2017
DOI: 10.5433/1679-0359.2017v38n5p2921
|View full text |Cite
|
Sign up to set email alerts
|

Carbon fractions and soil fertility affected by tillage and sugarcane residue management an Xanthic Udult

Abstract: The gradual change in management practices in sugarcane (Saccharum spp.) production from burning straw to a green harvesting system, as well as the use of minimum soil tillage during field renovation, may affect soil fertility and soil organic matter (SOM) contents. The objectives of this work were to investigate the influence of sugar cane production systems on: (1) soil fertility parameters; (2) on physical carbon fractions; (3) and on humic substance fractions, in a long-term experiment, comparing two soil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…It was in accordance with data shown by [50], which a portion of C derived from straw enters into the soil as labile organic C pool. Additionally, a greater protection and increase in C in humic substance fractions in areas where there is a minimum tillage of soil was reported by Lopes [59]. Studies using stable isotopes of C (δ 13 C) have shown that a greater proportion (about 60%) of soil C is derived from the straw in the sugarcane field, which indicates that the humification process was stimulated [54].…”
Section: Discussionmentioning
confidence: 83%
“…It was in accordance with data shown by [50], which a portion of C derived from straw enters into the soil as labile organic C pool. Additionally, a greater protection and increase in C in humic substance fractions in areas where there is a minimum tillage of soil was reported by Lopes [59]. Studies using stable isotopes of C (δ 13 C) have shown that a greater proportion (about 60%) of soil C is derived from the straw in the sugarcane field, which indicates that the humification process was stimulated [54].…”
Section: Discussionmentioning
confidence: 83%
“…Los Andisoles se caracterizan por su alto contenido de MO, propio del desarrollo del complejo aluminio-humus (Malagón et al, 1991) sin embargo, esta MO es susceptible al manejo, disminuyendo su contenido de manera significativa por acción de la continua labranza del suelo (arado de discos y arado rotatorio) y el monocultivo (Shoji, et al, 1993;Lopes et al, 2017;Silva et al, 2007). Sin embargo, como muestran nuestros resultados, se logra incrementar la MO con periodos relativamente cortos de barbecho, 5 años, aunque la tasa de incremento posterior a este período disminuye.…”
Section: Resultados Y Discusiónunclassified
“…This negative variation in StockC in the 0-0.05-m layer is more evident in the SC area. This is mainly due to the intense soil management in the SC area, where gradation is used for crop renewal (Lopes et al, 2017). This process breaks the soil aggregates, leaving the SOM exposed to microorganisms that consume this organic matter, releasing CO 2 (Bertollo and Levien, 2019;Gonçalves et al, 2019).…”
Section: Resultsmentioning
confidence: 99%